Light absorbing composition and optical filter

By using alkoxysilane in the light absorbing composition to form the siloxane bonding framework and organic functional groups, the problem of insufficient flexibility of the filter light absorbing layer is solved, and higher processing reliability and moisture resistance are achieved.

CN113677687BActive Publication Date: 2025-04-25NIPPON SHEET GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080027825.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-04-18
Filing Date
2020-04-17
Publication Date
2025-04-25
Estimated Expiration
2040-04-17

AI Technical Summary

Technical Problem

The light absorbing layer of the existing filter has insufficient flexibility, which leads to prone to cracking or wrinkling during processing and bonding, making it difficult to adapt to complex imaging device designs.

Method used

A light absorbing composition containing a light absorber, a curable resin and alkoxysilane is used to form a skeleton with a siloxane bond through hydrolysis and condensation reaction of alkoxysilane, and the organic functional groups of dialkoxysilane are combined to impart flexibility and moisture resistance to the light absorbing layer.

Benefits of technology

It improves the softness and moisture resistance of the light absorbing layer, reduces the risk of damage during processing and thermal expansion and contraction, and adapts to the design needs of complex imaging devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003296868710000051
    Figure BDA0003296868710000051
  • Figure BDA0003296868710000171
    Figure BDA0003296868710000171
  • Figure BDA0003296868710000181
    Figure BDA0003296868710000181
Patent Text Reader

Abstract

The light-absorbing composition of the present invention contains a light absorber, a curable resin, and an alkoxysilane. The alkoxysilane includes a dialkoxysilane. Since the alkoxysilane of the light-absorbing composition includes a dialkoxysilane, a strong skeleton having a siloxane bond is formed in the light-absorbing layer, and the organic functional group of the dialkoxysilane easily imparts the desired flexibility to the light-absorbing layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to light absorbing compositions and optical filters. Background Art

[0002] In an imaging device using a solid-state imaging element such as a CCD (Charge Coupled Device) or a CMOS (Complementary Metal Oxide Semiconductor), various filters are arranged in front of the solid-state imaging element in order to obtain an image with good color reproducibility. Generally, a solid-state imaging element has spectral sensitivity in a wide wavelength range from the ultraviolet region to the infrared region. On the other hand, human visual sensitivity exists only in the visible light region. Therefore, in order to make the spectral sensitivity of the solid-state imaging element in the imaging device close to the visual sensitivity of the human being, it is known to have a technology of arranging a filter in front of the solid-state imaging element to shield a part of the infrared or ultraviolet light.

[0003] In the past, as such filters, filters that shield infrared or ultraviolet rays by utilizing light reflection based on dielectric multilayer films are common. On the other hand, in recent years, filters having a film containing a light absorber have attracted people's attention. The transmittance characteristics of the filter having a film containing a light absorber are not easily affected by the incident angle, so even if light is incident on the filter at an angle in an imaging device, a good image with little color change can be obtained. In addition, a light absorption filter that does not use a light reflecting film can suppress the occurrence of ghosting or light shifting caused by multiple reflections based on the light reflecting film, so it is easy to obtain a good image when shooting in a backlit state or night scene. In addition, a filter having a film containing a light absorber is also advantageous from the perspective of miniaturization and thinning of the imaging device.

[0004] For example, Patent Document 1 describes an optical filter having a UV-IR absorbing layer capable of absorbing infrared and ultraviolet rays. The UV-IR absorbing layer contains a UV-IR absorber formed of phosphonic acid and copper ions. In addition, Patent Document 2 describes an infrared cutoff filter having an organic pigment layer and a phosphonate copper layer.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 6232161

[0008] Patent Document 2: Japanese Patent No. 6281023 Summary of the invention

[0009] Problems to be solved by the invention

[0010] The techniques described in Patent Documents 1 and 2 have room for further research from the perspective of imparting desired flexibility to the light absorbing layer in the optical filter. Therefore, the present invention provides a light absorbing composition that is advantageous from the perspective of imparting desired flexibility to the light absorbing layer in the optical filter. In addition, the present invention provides an optical filter having a light absorbing layer having desired flexibility.

[0011] Means for solving problems

[0012] The present invention provides a light absorbing composition comprising:

[0013] Light absorbers;

[0014] a curable resin; and

[0015] Alkoxysilane,

[0016] The alkoxysilane mentioned above includes dialkoxysilane.

[0017] The present invention also provides an optical filter comprising a light-absorbing layer formed from a cured product of the light-absorbing composition.

[0018] In addition, the present invention provides an optical filter,

[0019] The invention comprises a light absorbing layer containing a light absorber and a hydrolyzed condensate of alkoxysilane.

[0020] When one main surface of the light absorbing layer was measured by a nanoindentation method (continuous rigidity measurement method) using a nanoindenter, the average value of the Young's modulus was 2.00 GPa or less, and the average value of the hardness was 0.06 GPa or less.

[0021] Effects of the Invention

[0022] The above-mentioned light-absorbing composition is advantageous in that it imparts desired flexibility to the light-absorbing layer in the optical filter. In addition, the light-absorbing layer of the above-mentioned optical filter has desired flexibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cross-sectional view showing an example of the optical filter of the present invention.

[0024] Figure 2 This is a cross-sectional view showing another example of the optical filter of the present invention.

[0025] Figure 3 : is the transmittance spectrum of the filter of Example 1.

[0026] Figure 4 : is the transmittance spectrum of the filter of Example 2.

[0027] Figure 5 : is the transmittance spectrum of the filter of Example 3.

[0028] Figure 6 : is the transmittance spectrum of the filter of Comparative Example 1.

[0029] Figure 7 3 and 4 are transmittance spectra of the optical filter of Example 1 before and after the humidity resistance test.

[0030] Figure 8 It is the transmittance spectrum of the optical filter of Example 2 before and after the humidity resistance test. DETAILED DESCRIPTION

[0031] As optical filters having a light absorbing layer, there are known types of filters that are composed of a light absorbing layer alone, and filters that have a light absorbing layer formed on a substrate such as glass or resin. In the case of the former type of optical filter, if the light absorbing layer is hard or has a high hardness like glass, the flexibility of the light absorbing layer is easily reduced. For example, when the filter is bent or mechanically deformed, the light absorbing layer may be cracked or wrinkled. In the case of the latter type of optical filter that has a light absorbing layer formed on a flexible substrate such as resin, when the filter is similarly deformed, the light absorbing layer may also be cracked or wrinkled. Therefore, it is necessary to be very careful when handling these filters.

[0032] When cutting a filter formed in a large area to make a chip in the manufacturing process, a large-scale slicer or other equipment for glass cutting is required. In addition, when cutting the filter, it is sometimes necessary to study the problems associated with the properties of the glass material, namely cracks or broken edges. In addition, when it is desired to arrange the filter on a sensor such as a solid-state imaging element for bonding, if the filter is hard, it is sometimes difficult to arrange the filter and bond it due to the inherent warping (uneven flatness) of the filter. In order to facilitate such processing, it is advantageous to increase the softness of the light absorbing layer.

[0033] Therefore, the present inventors have repeatedly conducted day and night studies on a technology that is advantageous in terms of imparting desired flexibility to a light absorbing layer, and have developed the light absorbing composition and optical filter of the present invention.

[0034] The following is a description of an embodiment of the present invention. It should be noted that the following description is related to an example of the present invention, and the present invention is not limited to these examples.

[0035] The light absorbing composition of the present invention contains a light absorber, a curable resin and an alkoxysilane. In addition, the alkoxysilane includes a dialkoxysilane.

[0036] When a light absorbing layer is formed using a light absorbing composition, a silanol group is generated by the hydrolysis of an alkoxysilane. The generated compound from an alkoxysilane having a silanol group further reacts and undergoes polycondensation, thereby forming a strong skeleton having a siloxane bond (-Si-O-Si-). If the organic component (organic functional group) in the substance having the skeleton is small, the formed light absorbing layer is difficult to have the desired flexibility. In this case, when a strong pressure is applied locally in the light absorbing layer, the skeleton having a siloxane bond is prone to break. However, since the alkoxysilane of the light absorbing composition contains dialkoxysilane, while a strong skeleton having a siloxane bond is formed in the light absorbing layer, the light absorbing layer is easily given the desired flexibility by the organic functional group possessed by the dialkoxysilane. Therefore, for example, when the light absorbing layer formed using the light absorbing composition is cut, cracks and edge collapse are not easy to occur. In addition, even if the light absorbing layer formed using the light absorbing composition is bent, the light absorbing layer is not easy to break.

[0037] For example, it is considered to provide a filter in which a light-absorbing composition is coated on a solid-state imaging element or optical component such as a CCD and a CMOS and is integrated with the imaging element or optical component. When the filter integrated with the imaging element or optical component is placed in a specific thermal cycle environment, thermal expansion and thermal contraction may occur. The light-absorbing layer formed using the light-absorbing composition is easy to have the desired softness and is easy to deform in accordance with thermal expansion and thermal contraction. Therefore, it is easy to suppress the breakage and damage of the light-absorbing layer.

[0038] Furthermore, for highly flexible filters, after being manufactured as filters with flat surfaces, when assembled into an optical system, it is possible to bend along the configuration surface forming a curve to form a curved surface. By making the main surface of the filter a curved surface, it is also possible to cope with the design of special imaging devices based on complex sensor configurations.

[0039] Dialkoxysilane is not limited to a specific one. Dialkoxysilane has, for example, a hydrocarbon group having 1 to 6 carbon atoms bonded to a silicon atom. Alkoxysilane may also have a halogenated hydrocarbon group in which at least one hydrogen atom in the hydrocarbon group having 1 to 6 carbon atoms bonded to a silicon atom is substituted by a halogen atom. In this case, it is easy to further impart the desired flexibility to the light absorbing layer formed using the light absorbing composition.

[0040] The dialkoxysilane may be, for example, an alkoxysilane represented by the following formula (b): In this case, it is easy to more reliably impart desired flexibility to the light-absorbing layer formed using the light-absorbing composition.

[0041] (R2)2-Si-(OR3)2 (b)

[0042] [In the formula, R2 is independently an alkyl group having 1 to 6 carbon atoms, and R3 is independently an alkyl group having 1 to 8 carbon atoms.]

[0043] The dialkoxysilane may be, for example, dimethyldiethoxysilane, dimethyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, or 3-glycidoxypropylmethyldiethoxysilane.

[0044] In the light-absorbing composition, the alkoxysilane may further contain at least one of tetraalkoxysilane and trialkoxysilane. This makes it easy to form a dense structure by siloxane bonds in the light-absorbing layer formed using the light-absorbing composition.

[0045] In the light-absorbing composition, the alkoxysilane may further contain tetraalkoxysilane and trialkoxysilane. This makes it easier and more reliable to form a dense structure by siloxane bonds in the light-absorbing layer formed using the light-absorbing composition.

[0046] In the light absorbing composition, at least one of the tetraalkoxysilane and the trialkoxysilane is not limited to a specific alkoxysilane. For example, in the light absorbing composition, the alkoxysilane is at least one selected from the group consisting of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, n-propyltriethoxysilane, n-propyltrimethoxysilane, hexyltriethoxysilane, hexyltrimethoxysilane, trifluoropropyltriethoxysilane, trifluoropropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane.

[0047] The content of dialkoxysilane in the alkoxysilane is not limited to a specific value. The content of dialkoxysilane in the alkoxysilane is, for example, 15 to 48% by mass when the alkoxysilane is converted into a completely hydrolyzed condensate. This makes it easier and more reliable to impart the desired flexibility to the light absorbing layer formed using the light absorbing composition.

[0048] The content of dialkoxysilane in the alkoxysilane is preferably 15 to 20% by mass when the alkoxysilane is converted into a completely hydrolyzed condensate. As a result, the light absorbing layer formed using the light absorbing composition is likely to exhibit high moisture resistance. The reason is that the light absorber is not likely to aggregate in a high humidity environment because of the dense structure formed by the siloxane bond.

[0049] The light absorber is not limited to a specific light absorber as long as it can absorb light of a specific wavelength. The light absorber can be formed of, for example, phosphonic acid represented by the following formula (a) and copper ions.

[0050] [Chemistry 1]

[0051]

[0052] [Where R 11 It is an alkyl group, an aryl group, a nitroaryl group, a hydroxyaryl group, or a halogenated aryl group in which at least one hydrogen atom in the aryl group is substituted with a halogen atom.]

[0053] In the light-absorbing composition, for example, the phosphonic acid represented by formula (a) is coordinated to the copper ion to form a light absorber. In addition, for example, microparticles containing at least a light absorber are formed in the light-absorbing composition. In this case, due to the action of alkoxysilane, the microparticles will not agglomerate but will be dispersed in the light-absorbing composition. The average particle size of the microparticles is, for example, 5nm to 200nm. If the average particle size of the microparticles is 5nm or more, no special process for miniaturization of the microparticles is required, and the possibility of the structure of the microparticles containing at least the light absorber being destroyed is small. In addition, in the light-absorbing composition, the microparticles are well dispersed. In addition, if the average particle size of the microparticles is 200nm or less, the influence caused by Mie scattering can be reduced, the transmittance of visible light in the filter can be increased, and the reduction of characteristics such as contrast and haze of the image captured by the imaging device can be suppressed. The average particle size of the microparticles is preferably 100nm or less. In this case, since the influence caused by Rayleigh scattering is reduced, the transparency of the filter made using the light-absorbing composition to visible light is increased. In addition, the average particle size of the microparticles is more preferably 75 nm or less. In this case, the optical filter produced using the light absorbing composition has particularly high transparency to visible light. It should be noted that the average particle size of the microparticles can be measured by dynamic light scattering.

[0054] As a dispersant for the light absorber, a phosphoric acid ester is sometimes used. Therefore, the light absorbing composition may also contain a phosphoric acid ester. On the other hand, in the light absorbing layer formed using the light absorbing composition, the compound derived from the alkoxysilane can appropriately disperse the light absorber while imparting high moisture resistance to the light absorbing layer compared to the phosphoric acid ester. Therefore, by making the light absorbing composition contain an alkoxysilane, the amount of the phosphoric acid ester can be reduced. In the formation of the light absorbing layer, the alkoxysilane present around the light absorber reacts with the dialkoxysilane, and the light absorbing layer is easily homogeneous and has high density. It should be noted that the light absorbing composition may not contain a phosphoric acid ester.

[0055] Phosphate esters are, for example, phosphate esters having a polyoxyalkyl group. Phosphate esters having a polyoxyalkyl group are not limited to specific phosphate esters. Phosphate esters having a polyoxyalkyl group are, for example, Plysurf A208N: polyoxyethylene alkyl (C12, C13) ether phosphate, Plysurf A208F: polyoxyethylene alkyl (C8) ether phosphate, Plysurf A208B: polyoxyethylene lauryl ether phosphate, Plysurf A219B: polyoxyethylene lauryl ether phosphate, Plysurf AL: polyoxyethylene styrenated phenyl ether phosphate, Plysurf A212C: polyoxyethylene tridecyl ether phosphate, or Plysurf A215C: polyoxyethylene tridecyl ether phosphate. They are all products manufactured by Daiichi Kogyo Seiyaku Co., Ltd. The phosphoric acid ester may be, for example, NIKKOL DDP-2: polyoxyethylene alkyl ether phosphate, NIKKOL DDP-4: polyoxyethylene alkyl ether phosphate, or NIKKOL DDP-6: polyoxyethylene alkyl ether phosphate, all of which are products manufactured by Nikkol Chemicals.

[0056] In the light-absorbing composition, the curable resin is not limited to a specific resin. The curable resin is, for example, a silicone resin. The silicone resin is a compound having a siloxane bond in its structure. In this case, since the hydrolysis polycondensate of alkoxysilane also has a siloxane bond, the hydrolysis polycondensate of alkoxysilane and the curable resin have good compatibility in the light-absorbing layer formed using the light-absorbing composition.

[0057] The resin is preferably a silicone resin containing an aromatic group such as a phenyl group. If the resin contained in the optical filter is rigid, as the thickness of the layer containing the resin increases, cracks are easily generated due to curing shrinkage in the manufacturing process of the optical filter. If the resin is a silicone resin containing an aromatic group, the layer formed by the light-absorbing composition is likely to have good crack resistance. In addition, the silicone resin containing an aromatic group has high compatibility with the phosphonic acid represented by formula (a), and the light absorber is not easy to agglomerate. Specific examples of silicone resins used as matrix resins include KR-255, KR-300, KR-2621-1, KR-211, KR-311, KR-216, KR-212, KR-251 and KR-5230. They are all silicone resins manufactured by Shin-Etsu Chemical Co., Ltd.

[0058] An example of a method for preparing a light absorbing composition will be described by taking the case where the light absorber is formed of the above-mentioned phosphonic acid and copper ions as an example.

[0059] For example, the light absorbing composition contains R 11In the case of a phosphonic acid (aryl phosphonic acid) of an aryl group, a nitroaryl group, a hydroxyaryl group, or a halogenated aryl group, liquid D is prepared as follows. A copper salt such as copper acetate monohydrate is added to a prescribed solvent such as tetrahydrofuran (THF) and stirred to prepare liquid A, which is a solution of the copper salt. Next, the aryl phosphonic acid is added to a prescribed solvent such as THF and stirred to prepare liquid B. In the case of using two or more aryl phosphonic acids as the phosphonic acid represented by formula (a), each aryl phosphonic acid can be added to a prescribed solvent such as THF, and then stirred to mix two or more preparatory solutions prepared for each type of aryl phosphonic acid to prepare liquid B. For example, alkoxysilane is added to the preparation of liquid B. While stirring liquid A, liquid B is added to liquid A and stirred for a prescribed time. Next, a prescribed solvent such as toluene is added to the solution and stirred to obtain liquid C. Next, while heating liquid C, a desolventizing treatment is performed for a prescribed time to obtain liquid D. Thus, solvents such as THF and acetic acid (boiling point: about 118°C) and other components generated by the dissociation of copper salts are removed, and the phosphonic acid represented by formula (a) and copper ions are used to generate a light absorber. The temperature at which the C solution is heated is determined based on the boiling point of the components to be removed from the copper salt. It should be noted that in the desolventizing treatment, solvents such as toluene (boiling point: about 110°C) used to obtain the C solution will also evaporate. The solvent preferably remains in the light-absorbing composition to a certain extent, so the amount of solvent added and the time of the desolventizing treatment can be determined from this aspect. It should be noted that in order to obtain the C solution, o-xylene (boiling point: about 144°C) can also be used instead of toluene. In this case, since the boiling point of o-xylene is higher than that of toluene, the amount added can be reduced to about one-fourth of the amount of toluene added.

[0060] The light absorbing composition contains R in formula (a) 11In the case of an alkyl phosphonic acid (alkyl phosphonic acid), for example, liquid H can be further prepared as follows. First, a copper salt such as copper acetate monohydrate is added to a prescribed solvent such as tetrahydrofuran (THF) and stirred to obtain liquid E, which is a solution of a copper salt. In addition, an alkyl phosphonic acid is added to a prescribed solvent such as THF and stirred to prepare liquid F. In the case of using two or more phosphonic acids as the alkyl phosphonic acid, each alkyl phosphonic acid can be added to a prescribed solvent such as THF, and then stirred to mix two or more preliminaries prepared for each type of alkyl phosphonic acid to prepare liquid F. For example, alkoxysilane is further added to the preparation of liquid F. While stirring liquid E, liquid F is added to liquid E and stirred for a prescribed time. Next, a prescribed solvent such as toluene is added to the solution and stirred to obtain liquid G. Next, while heating liquid G, a desolventizing treatment is performed for a prescribed time to obtain liquid H. Thus, components produced by the dissociation of the copper salt such as solvents such as THF and acetic acid are removed. The temperature for heating liquid G is determined in the same manner as that for liquid C, and the solvent for obtaining liquid G is also determined in the same manner as that for liquid C.

[0061] For example, liquid D and liquid H are mixed at a predetermined ratio, and alkoxysilane is added, and a curable resin such as a silicone resin is added as needed to prepare a light absorbing composition. In this case, dialkoxysilane can be added after liquid D and liquid H are mixed.

[0062] like Figure 1 As shown, the filter 1a has a light absorbing layer 10. The light absorbing layer 10 contains a light absorber and a hydrolysis condensate of alkoxysilane. The light absorbing layer 10 is characterized by its soft properties. For example, when a main surface 10a of the light absorbing layer 10 is measured using a nanoindenter according to the nanoindentation method (continuous rigidity measurement method), the average value of the Young's modulus is less than 2.00 GPa. The average value of the Young's modulus can be, for example, 0.10 to 2.00 GPa. In addition, the average value of the hardness is less than 0.06 GPa. The average value of the hardness can be 0.005 to 0.06 GPa. In this way, the light absorbing layer 10 contains a skeleton having a siloxane bond through the hydrolysis condensate of alkoxysilane and has the desired softness. For details about the nanoindentation method (continuous rigidity measurement method), reference can be made to International Publication No. 2019 / 044758 and Japanese Patent Publication No. 2015-174270.

[0063] The hydrolysis-condensation product of alkoxysilane contained in the light-absorbing layer 10 includes, for example, a hydrolysis-condensation product of dialkoxysilane. Thus, the light-absorbing layer 10 has desired flexibility.

[0064] From another aspect, the light absorbing layer 10 may be formed of, for example, a cured product of the light absorbing composition described above. In this case, the light absorbing layer 10 is likely to have desired flexibility.

[0065] When a humidity test is performed in which the filter 1a is kept at a temperature of 85°C and a relative humidity of 85% for 1000 hours, the filter 1a satisfies the following conditions, for example. In this case, the filter 1a shows good humidity resistance. It should be noted that, with respect to each parameter, the "change amount" refers to the absolute value of the difference between the parameter values ​​before and after the humidity test. The "change amount of average transmittance" represents the absolute value of the difference between the average value of the transmittance before the humidity test and the average value of the transmittance after the humidity test in a specific wavelength range. The "change amount of maximum transmittance" represents the absolute value of the difference between the maximum value of the transmittance before the humidity test and the maximum value of the transmittance after the humidity test in a specific wavelength range. In addition, the unit of the change amount of the relevant parameter of the transmittance expressed as a percentage is expressed as a "percentage point".

[0066] (i) Change in average transmittance ΔT at wavelengths of 450 to 600 nm 450-600 Less than 3 percentage points. 450-600 It is preferably 1 percentage point or less, and more preferably 0.5 percentage point or less.

[0067] (ii) The change in UV cutoff wavelength Δλuvc is less than 5 nm, and the change in IR cutoff wavelength Δλirc is less than 5 nm. It should be noted that the UV cutoff wavelength is a wavelength at which the transmittance reaches 50% in the wavelength range of 350 nm to 450 nm. The IR cutoff wavelength is a wavelength at which the transmittance reaches 50% in the wavelength range of 600 nm to 800 nm.

[0068] (iii) The amount of change Δλirc-uvc obtained by subtracting the UV cutoff wavelength from the IR cutoff wavelength is 10 nm or less.

[0069] (iv) Change in maximum transmittance ΔT at wavelengths of 300 to 350 nm max300-350 Less than 1 percentage point. max300-350 Preferably, it is 0.5 percentage points or less.

[0070] (v) Change in maximum transmittance ΔT at wavelengths of 300 to 360 nm max300-360 Less than 1 percentage point. max300-360 Preferably, it is 0.5 percentage points or less.

[0071] (vi) Change in average transmittance ΔT at wavelengths of 700 to 750 nm AVE700-750 Less than 3 percentage points. AVE700-750 Preferably, it is 1 percentage point or less.

[0072] (vii) Change in maximum transmittance ΔT at wavelengths of 750 to 1080 nm max750-1080 Less than 3 percentage points. max750-1080 Preferably, it is 1 percentage point or less.

[0073] (viii) Change in maximum transmittance ΔT in the wavelength range of 800 to 950 nm max800-950 , the change in maximum transmittance ΔT in the wavelength range of 800 to 1000 nm max800-1000 , the change in maximum transmittance ΔT in the wavelength range of 800 to 1050 nm max800-1050 , the change in maximum transmittance ΔT in the wavelength range of 800 to 1100 nm max800-1100 , the change in maximum transmittance ΔT in the wavelength range of 800 to 1150 nm max800-1150 , and the change in maximum transmittance ΔT in the wavelength range of 800 to 1200 nm max800-1200 They were less than 3 percentage points respectively. max800-950 , ΔT max800-1000 , ΔT max800-1050 , ΔT max800-1100 , ΔT max800-1150 , and ΔT max800-1200 Preferably, they are 1 percentage point or less respectively.

[0074] like Figure 1 As shown, the optical filter 1a is composed of, for example, a single light absorbing layer 10. In this case, the optical filter 1a is used separately from, for example, an imaging element or an optical component. The optical filter 1a may also be bonded to the imaging element and the optical component. On the other hand, the optical filter 1a may be formed by applying the above-mentioned light absorbing composition to the imaging element or the optical component and curing the light absorbing composition.

[0075] The optical filter 1a is produced, for example, by peeling off the light absorbing layer 10 formed on a substrate. In this case, the material of the substrate may be glass, resin, or metal. The surface of the substrate may be subjected to surface treatment such as coating with a fluorine-containing compound.

[0076] The filter 1a can be, for example, Figure 2 The optical filter 1b shown in FIG. 1 is modified. The optical filter 1b is constructed in the same manner as the optical filter 1a except for the cases where special instructions are given. The components of the optical filter 1b that are the same as or correspond to the components of the optical filter 1a are given the same reference numerals, and detailed descriptions are omitted. Unless there is a technical contradiction, the description of the optical filter 1a is also applicable to the optical filter 1b.

[0077] like Figure 2As shown in FIG. 1 , the optical filter 1b includes a light absorbing layer 10 and a transparent dielectric substrate 20. The light absorbing layer 10 is formed parallel to one main surface of the transparent dielectric substrate 20. The light absorbing layer 10 may be in contact with one main surface of the transparent dielectric substrate 20, for example. In this case, the light absorbing layer 10 is formed by, for example, applying the above-mentioned light absorbing composition to one main surface of the transparent dielectric substrate 20 and curing the light absorbing composition.

[0078] The type of the transparent dielectric substrate 20 is not limited to a specific type. The transparent dielectric substrate 20 may have an absorption capability in the infrared region. The transparent dielectric substrate 20 may have an average spectral transmittance of 90% or more in a wavelength range of 350 nm to 900 nm, for example. The material of the transparent dielectric substrate 20 is not limited to a specific material, and may be, for example, a specific glass or resin. When the material of the transparent dielectric substrate 20 is glass, the transparent dielectric substrate 20 may be, for example, transparent glass made of silicate glass such as soda-lime glass and borosilicate glass, or infrared cutoff glass. The infrared cutoff glass may be, for example, phosphate glass or fluorophosphate glass containing CuO.

[0079] When the material of transparent dielectric substrate 20 is a resin, the resin is, for example, a cyclic olefin resin such as a norbornene resin, a polyarylate resin, an acrylic resin, a modified acrylic resin, a polyimide resin, a polyetherimide resin, a polysulfone resin, a polyethersulfone resin, a polycarbonate resin, or a silicone resin.

[0080] The optical filters 1a and 1b may be modified so as to further include other functional films such as infrared reflective films.

[0081] Example

[0082] The present invention is described in more detail by way of examples. It should be noted that the present invention is not limited to the following examples.

[0083] <Example 1>

[0084] (Preparation of Aryl Copper Phosphonate)

[0085] 4.500g of cupric acetate monohydrate was mixed with 240g of tetrahydrofuran (THF) and stirred for 3 hours to obtain a cupric acetate solution. Then, 1.646g of Plysurf A208N (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as a phosphate compound was added to the obtained cupric acetate solution, and stirred for 30 minutes to obtain liquid A. 40g of THF was added to 0.706g of phenylphosphonic acid, and stirred for 30 minutes to obtain liquid B-1. 40g of THF was added to 4.230g of 4-bromophenylphosphonic acid, and stirred for 30 minutes to obtain liquid B-2. Then, liquid B-1 was mixed with liquid B-2, and stirred for 1 minute. 8.664g of methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) and 2.830g of tetraethoxysilane (TEOS) (special grade manufactured by Kishida Chemical Co., Ltd.) were added to the mixed solution, and stirred for 1 minute to obtain liquid B. While stirring liquid A, add liquid B to liquid A, and stir at room temperature for 1 minute. Next, add 140 g of toluene to the solution, stir at room temperature for 1 minute to obtain liquid C. The liquid C is placed in a flask, heated with an oil bath (manufactured by Tokyo Rika Instruments Co., Ltd., model: OSB-2100), and desolventized with a rotary evaporator (manufactured by Tokyo Rika Instruments Co., Ltd., model: N-1110SF). The set temperature of the oil bath is adjusted to 105°C. Thereafter, the desolventized liquid D of Example 1 is taken out from the flask. In the desolventizing treatment, the desolventizing treatment is carried out in a manner that the viscosity is reduced to a certain degree without completely removing the solvent. In this way, liquid D, which is a dispersion of aromatic copper phosphonate (UV-IR absorber), is obtained.

[0086] (Production of Alkyl Copper Phosphonate)

[0087] 4.500 g of copper acetate monohydrate was mixed with 240 g of THF and stirred for 3 hours to obtain a copper acetate solution. Then, 2.572 g of Plysurf A208N as a phosphate compound was added to the obtained copper acetate solution, and stirred for 30 minutes to obtain liquid E. And 40 g of THF was added to 2.886 g of n-butylphosphonic acid, and stirred for 30 minutes to obtain liquid F. While stirring liquid E, liquid F was added to liquid E and stirred at room temperature for 1 minute. Then, 100 g of toluene was added to the solution, and stirred at room temperature for 1 minute to obtain liquid G. Liquid G was placed in a flask, heated with an oil bath, and desolventized using a rotary evaporator. The set temperature of the oil bath was adjusted to 105°C. Thereafter, liquid H of Example 1 after desolventization was taken out from the flask. In the desolventization treatment, the desolventization treatment was carried out in a manner that the viscosity of liquid H was reduced to a certain extent without completely removing the solvent. Thus, liquid H which is a dispersion liquid of copper butylphosphonate (IR absorber) was obtained.

[0088] (Production of Light-Absorbing Composition)

[0089] 12.57 g of a silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to liquid D, and the mixture was stirred for 30 minutes to obtain liquid I. An amount corresponding to 40% by mass of the total amount of liquid H was added to liquid I, and 10.840 g of methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) as an alkoxysilane, 5.660 g of tetraethoxysilane (TEOS) (special grade manufactured by Kishida Chemical Co., Ltd.), and 4.896 g of dimethyldiethoxysilane (DMDES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-22) were further added thereto, and the mixture was stirred for 30 minutes to obtain the light absorbing composition of Example 1. The light absorbing composition of Example 1 was prepared as follows: assuming that a completely hydrolyzed condensate of alkoxysilane was obtained, the content of the silane compound derived from MTES was 60.0%, the content of the silane compound derived from TEOS was 20.0%, and the content of the silane compound derived from DMDES was 20.0% by mass in the completely hydrolyzed condensate of alkoxysilane. It should be noted that the calculation was performed based on the following premises: the ratio of the amount of the silane compound derived from MTES (solid content) present in the completely hydrolyzed condensate of alkoxysilane to the amount of MTES added was 37.64% by mass; the ratio of the amount of the silane compound derived from TEOS (solid content) present in the completely hydrolyzed condensate of alkoxysilane to the amount of TEOS added was 28.84% by mass; and the ratio of the amount of the silane compound derived from DMDES (solid content) present in the completely hydrolyzed condensate of alkoxysilane to the amount of DMDES added was 50.01% by mass. The calculation was performed under the same premise in Examples 2 and 3 and Comparative Example 1. Table 2 shows the relationship between the amount of alkoxysilane added in the preparation of liquid D and the preparation of the light absorbing composition.

[0090] (Production of optical filters)

[0091] 0.1 g of a surface antifouling coating agent (manufactured by Daikin Industries, Ltd., product name: OPTOOL DSX, active ingredient concentration: 20% by mass) was mixed with 19.9 g of a hydrofluoroether solution (manufactured by 3M, product name: Novec 7100) and stirred for 5 minutes to prepare a fluorine treatment agent (active ingredient concentration: 0.1% by mass). The fluorine treatment agent was overflow-coated on a circular borosilicate glass (manufactured by SCHOTT, product name: D263 T eco) with a diameter of 200 mm and a thickness of 0.7 mm. The glass substrate was then placed at room temperature for 24 hours to dry the coating of the fluorine treatment agent, and then the glass surface was gently wiped with a dust-free cloth containing Novec 7100 to remove excess fluorine treatment agent. In this way, a fluorine treatment substrate was prepared.

[0092] The light-absorbing composition of Example 1 is applied to a fluorine-treated substrate using an applicator. At this time, a stainless steel template (internal dimensions: about 100 mm square) is used to apply the coating so that the coating can maintain a sufficient thickness. The substrate coated with the light-absorbing composition is allowed to stand for a specified time to allow the components of the light-absorbing composition to react sufficiently, and then the substrate is slowly heated from room temperature to slowly evaporate the solvent and cure the light-absorbing composition. The maximum temperature reached during the heating is adjusted to 85°C. The substrate is further placed in an environment of a temperature of 85°C and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane and obtain a light-absorbing film. For the light-absorbing film obtained in this way, its end is lifted and peeled off from the substrate to obtain the filter of Example 1 having a size of about 100 mm square when viewed from above.

[0093] (Filter cutting)

[0094] The filter of Example 1 was cut into long strips using a rotary cutter (manufactured by Olfa) with a circular blade having a diameter of 28 mm. Specifically, a load of about 30 N was applied to the filter along four straight lines parallel to one side of the filter and positioned at intervals of 20 mm to cut the filter. The obtained long strip sample was observed at a magnification of 50 times using a metal microscope. As a result, no damage such as splitting or breaking occurred around the cross section of the sample, confirming that the filter of Example 1 was well cut.

[0095] <Example 2>

[0096] Liquid D, which is a dispersion of aryl copper phosphonate (UV-IR absorber), and liquid H, which is a dispersion of butyl copper phosphonate (IR absorber), were obtained in the same manner as in Example 1. Next, 12.57 g of a silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to liquid D, and the mixture was stirred for 30 minutes to obtain liquid I. An amount corresponding to 40% by mass of the total amount of liquid H was added to liquid I, and 5.420 g of methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) as an alkoxysilane, 2.830 g of tetraethoxysilane (TEOS) (special grade manufactured by Kishida Chemical Co., Ltd.), and 2.448 g of dimethyldiethoxysilane (DMDES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-22) were further added thereto, and the mixture was stirred for 30 minutes to obtain the light absorbing composition of Example 2. The light-absorbing composition of Example 2 was prepared in the following manner: assuming that a completely hydrolyzed condensate of alkoxysilane was obtained, the content of the silane compound derived from MTES was 65.0%, the content of the silane compound derived from TEOS was 20.0%, and the content of the silane compound derived from DMDES was 15.0%, based on mass.

[0097] The optical filter of Example 2 was prepared in the same manner as in Example 1 except that the light absorbing composition of Example 2 was used instead of the light absorbing composition of Example 1. The optical filter of Example 2 was further cut into a strip in the same manner as the optical filter of Example 1. The obtained strip sample was observed using a metal microscope at a magnification of 50 times. As a result, no damage such as splitting or breaking occurred around the cross section of the sample, and it was confirmed that the optical filter of Example 2 was well cut.

[0098] <Example 3>

[0099] Liquid D, which is a dispersion of aryl copper phosphonate (UV-IR absorber), and liquid H, which is a dispersion of butyl copper phosphonate (IR absorber), were obtained in the same manner as in Example 1. Next, 12.57 g of an organic silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to liquid D, and the mixture was stirred for 30 minutes to obtain liquid I. An amount corresponding to 40% by mass of the total amount of liquid H was added to liquid I, and 7.344 g of dimethyldiethoxysilane (DMDES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-22) was further added thereto as an alkoxysilane, and the mixture was stirred for 30 minutes to obtain a light-absorbing composition of Example 3. In the preparation of the light-absorbing composition of Example 3, methyltriethoxysilane (MTES) and tetraethoxysilane (TEOS) were not added to the mixed solution of liquid I and liquid H. The light-absorbing composition of Example 3 was prepared in the following manner: when it was assumed that a complete hydrolysis condensate of alkoxysilane was obtained, in the complete hydrolysis condensate of alkoxysilane, the content of silane compounds derived from MTES was 42.1%, the content of silane compounds derived from TEOS was 10.5%, and the content of silane compounds derived from DMDES was 47.4%, based on mass.

[0100] The optical filter of Example 3 was prepared in the same manner as in Example 1 except that the light-absorbing composition of Example 3 was used instead of the light-absorbing composition of Example 1. The optical filter of Example 3 was further cut into a strip in the same manner as the optical filter of Example 1. The obtained strip sample was observed using a metal microscope at a magnification of 50 times. As a result, no damage such as splitting or breaking occurred around the cross section of the sample, and it was confirmed that the optical filter of Example 3 was well cut.

[0101] <Comparative Example 1>

[0102] Liquid D, which is a dispersion of aryl copper phosphonate (UV-IR absorber), and liquid H, which is a dispersion of butyl copper phosphonate (IR absorber), were obtained in the same manner as in Example 1. Next, 12.57 g of an organic silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to liquid D, and stirred for 30 minutes to obtain liquid I. An amount corresponding to 40% by mass of the total amount of liquid H was added to liquid I, and stirring was further performed for 30 minutes to obtain a light-absorbing composition of Comparative Example 1. In the preparation of the light-absorbing composition of Comparative Example 1, no alkoxysilane was added to the mixed solution of liquid I and liquid H.

[0103] The optical filter of Comparative Example 1 was prepared in the same manner as in Example 1 except that the light-absorbing composition of Comparative Example 1 was used instead of the light-absorbing composition of Example 1. It was further attempted to cut the optical filter of Comparative Example 1 into a strip in the same manner as the optical filter of Example 1. However, a large number of cracks occurred around four straight lines parallel to one side of the filter and positioned at intervals of 20 mm, and the optical filter of Comparative Example 1 could not be cut well, and a strip-shaped sample could not be obtained.

[0104] <Transmittance Spectrum Measurement>

[0105] The transmittance spectra of each filter at an incident angle of 0° were measured using an ultraviolet-visible-near-infrared spectrophotometer (manufactured by JASCO Corporation, product name: V-670). The transmittance spectra of the filters of Example 1, Example 2, Example 3 and Comparative Example 1 are shown below: Figure 3 , Figure 4 , Figure 5 as well as Figure 6 In addition, Figures 3 to 6 The read transmittance-related characteristics are shown in Table 1.

[0106] <Thickness measurement>

[0107] The thickness of the filter was measured by measuring the distance from the filter surface using a laser displacement meter (manufactured by KEYENCE Corporation, product name: LK-H008). The results are shown in Table 1.

[0108] <Young's modulus and hardness>

[0109] The surface of the filter was measured according to the nanoindentation method (continuous rigidity measurement method) using a nanoindenter (manufactured by MTS Systems, product name: Nano Indenter XP). A diamond triangular pyramid indenter was used as the indenter, and the measurement was performed at room temperature of about 23°C and in the atmosphere. In the hardness-indentation depth graph obtained by the measurement, the hardness values ​​in the range of indentation depth of 5 to 10 μm were averaged to determine the average value of the surface hardness of each filter. In addition, in the Young's modulus-indentation depth graph obtained by the measurement, the Young's modulus values ​​in the range of indentation depth of 5 to 10 μm were averaged to determine the average value of the Young's modulus of each filter. In addition, considering that the main component of the filter is silicone resin, the Poisson's ratio of the filter was determined to be 0.4. The results are shown in Table 3. The average value of the Young's modulus in the example is 0.87 to 1.6 GPa, and the average value of the hardness is 0.020 to 0.048 GPa. On the other hand, in the comparative examples, the average value of the Young's modulus was 2.6 GPa and the hardness was 0.11 GPa, and it was found that the flexibility was poor.

[0110] <Measurement of Haze>

[0111] The haze of the optical filters of Examples 1 to 3 and the optical filter of Comparative Example 1 was measured using a haze meter (manufactured by Murakami Color Research Laboratory, product name: HM-65L2) in accordance with Japanese Industrial Standards JIS K 7136. Table 3 shows the results.

[0112] <Humidity resistance test>

[0113] The filters of Examples 1 to 3 were stored in a thermostatic hygrostat (manufactured by Tokyo Rikakii Co., Ltd., KCL-2000A) set at a temperature of 85°C and a relative humidity of 85% for 1000 hours to perform a humidity test. The transmittance spectra of the filters of Examples 1 and 2 after the humidity test at an incident angle of 0° were measured using an ultraviolet-visible near-infrared spectrophotometer (manufactured by JASCO Corporation, product name: V-670). The results are shown in Figure 7 and Figure 8 . Figure 7 and Figure 8 In the figure, the solid line represents the transmittance spectrum of the filter before the humidity test, and the dotted line represents the transmittance spectrum of the filter after the humidity test. The values ​​of the parameters read from these transmittance spectra are shown in Table 4. It should be noted that the filter of Example 3 after the humidity test was turbid and did not transmit any light.

[0114] Table 3 shows that the filters of Examples 1 to 3 have higher flexibility than the filter of Comparative Example 1. Table 4 shows that the filters of Examples 1 and 2 satisfy the above conditions (i) to (viii) and have good moisture resistance.

[0115] The light absorbing film of the optical filter according to the embodiment of the present invention has a small Young's modulus and high flexibility. Therefore, after the light absorbing film is formed on a flat substrate, it is peeled off from the substrate, and the peeled light absorbing film is laminated along the surface of other substrates having an arbitrary curved surface or a highly flexible flat surface such as a lens, a curved filter, a resinous highly flexible optical filter, or other optical elements, thereby making it possible to laminate the light absorbing film on the curved surface with a uniform thickness, and to form an optical element or optical filter having a light absorbing function.

[0116] In addition, in recent years, portable communication devices such as smartphones often use highly flexible substrates represented by displays using organic EL. The light absorbing film of the embodiment of the present invention can also exhibit conformability to such flexible displays or panels as substrates, and is therefore easily applicable to these fields.

[0117] In common coating methods such as spin coating or dip coating, forming a film of uniform thickness on a curved surface requires very precise control and is difficult to perform. On the other hand, according to the above method, a light absorbing film can be formed on a curved surface with uniform thickness relatively easily, and is therefore very effective.

[0118] An adhesive may be used to bond the light absorbing film to the curved surface. The pre-fired film may be laminated along the curved surface of the substrate, and then subjected to a heating treatment or a heating and humidification treatment. In the latter case, the pre-fired temperature is preferably below 60°C, and the final heating and humidification temperature is preferably above 80°C.

[0119] In addition, as a substrate for making a light-absorbing film, a substrate having a wire made of glass fiber, carbon fiber, cellulose nanofiber, etc. formed on the surface (for example, in a lattice shape) can be used. In this case, after the light-absorbing film is formed on the substrate, it is peeled off together with the wire, thereby obtaining a light-absorbing film having the wire formed inside or on the surface. Such a wire can give the light-absorbing film moderate mechanical rigidity, so that a light-absorbing film with flexibility and rigidity can be produced.

[0120] Furthermore, after forming a coating on a flat substrate, the substrate can be deformed and heated, or heated and humidified, to form the light absorbing film into a special surface state (e.g., lens shape) corresponding to the final substrate shape. By deforming or curing the light absorbing film in accordance with the desired substrate shape, light absorbing filters with various surface states (flat or curved) can be produced.

[0121] The light absorbing film as an embodiment of the present invention also has excellent impact resistance. Therefore, it has the advantage of not being easily restricted by the use environment. The light absorbing film as an embodiment of the present invention can be effectively used, for example, in a camera module, an optical sensor, or a part of various optical systems built into a wearable device exposed to long-term vibration or strong impact, especially a wearable camera or a sports camera.

[0122]

[0123]

[0124] [Table 3]

[0125]

[0126]

Claims

1. A light absorbing composition comprising: Light absorbers; a curable resin; and Alkoxysilane, The alkoxysilane includes dialkoxysilane and at least one of tetraalkoxysilane and trialkoxysilane, The dialkoxysilane is represented by (R2)2-Si-(OR3)2, R2 is independently an alkyl group having 1 to 6 carbon atoms, R3 is independently an alkyl group having 1 to 8 carbon atoms, The content of the dialkoxysilane in the alkoxysilane is 15% to 48% by mass when the alkoxysilane is converted into a completely hydrolyzed condensate. The light absorber comprises a phosphonic acid represented by the following formula (a) and copper ions, In the formula, R 11 It is an alkyl group, an aryl group, a nitroaryl group, a hydroxyaryl group, or a halogenated aryl group in which at least one hydrogen atom in the aryl group is substituted with a halogen atom.

2. The light-absorbing composition according to claim 1, wherein The R2 is a methyl group.

3. The light-absorbing composition according to claim 1 or 2, wherein The alkoxysilane further includes tetraalkoxysilane and trialkoxysilane.

4. The light-absorbing composition according to claim 1, wherein The content of the dialkoxysilane in the alkoxysilane is 15% to 20% by mass when the alkoxysilane is converted into a completely hydrolyzed condensate. 5 . An optical filter comprising a light-absorbing layer formed from a cured product of the light-absorbing composition according to claim 1 .

6. The optical filter according to claim 5, wherein When one main surface of the light absorbing layer is measured by a nanoindentation method (continuous rigidity measurement method) using a nanoindenter, the average value of the Young's modulus is 2.00 GPa or less, and the average value of the hardness is 0.06 GPa or less.

Citation Information

Patent Citations

  • Ink composition

    JP1987032161A

  • Liquid growth method

    JP1987081023A

  • Film having gas barrier property

    JP2015174270A

  • Polypropylene film, metallized film, and film capacitor

    WO2019044758A1

  • Near-infrared absorbing composition, method for manufacturing near-infrared cut filter, near-infrared cut filter, solid-state imaging element, camera module, infrared sensor, and infrared absorbing agent

    WO2017126528A1